Sexual Relationship Types, Partner HIV Self-Testing, and Pre-Exposure Prophylaxis Among South African Adolescent Girls and Young Women: A Latent Class Analysis. (1st April 2021) - Atkins, Kaitlyn; Rucinski, Katherine; Mudavanhu, Mutsa; Holmes, Leah; Mutunga, Lillian; Kaufman, Michelle R.; Bassett, Jean; Van Rie, Annelies; Schwartz, Sheree R.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Sexual relationships among adolescent girls and young women (AGYW) are influenced by social, economic, and gender dynamics. Understanding AGYW's different relationship types and their implications for HIV risk is important for development of tailored interventions. We sought to identify relationship typologies among AGYW and their impact on uptake of HIV prevention interventions. Methods: From May 2018 to February 2019, 2200 HIV-negative AGYW (ages 16–24) in Johannesburg, South Africa, participated in an HIV prevention intervention involving distribution of HIV self-test kits to their male partners. AGYW were also offered pre-exposure prophylaxis. At baseline, AGYW completed a questionnaire, and outcomes were assessed for 3 months. We used latent class analysis to identify relationship types and mixture modeling to estimate the impact of relationship type on engagement in prevention interventions. Results: We identified 3 relationship types: "stable, empowered relationships with older partners" (class 1, n = 973); "shorter, empowered relationships with peer partners" (class 2, n = 1067); and "shorter relationships with risky partners" (class 3, n = 160). Compared with AGYW in class 1 relationships, AGYW in class 2 and 3 relationships were less likely to complete partner testing alongside HIV results sharing (class 2 adjusted risk ratio: 0.89, 95% confidence interval: 0.85 to 0.95; class 3 adjusted risk ratio: 0.84, 95% confidence interval: 0.73 to 0.94). Pre-exposure prophylaxis uptake was highest in class 3 (11.2%) compared with class 2 (3.8%) and class 1 (1.0%; P < 0.001). Conclusions: Relationship type impacts uptake of HIV prevention interventions among South African youth. Intervention effectiveness could be optimized by using tailored approaches to HIV risk mitigation among AGYW.